2014
DOI: 10.1016/j.gaitpost.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Body-worn sensors capture variability, but not decline, of gait and balance measures in multiple sclerosis over 18 months

Abstract: Gait and balance deficits are a frequent complaint in MS but poorly captured by stopwatch-timed tests or rating scales. Body-worn accelerometers and gyroscopes are able to detect gait and balance abnormalities in people with MS who have normal walking speeds. Few longitudinal studies exist using this technology to study the evolution of mobility deficits. The purpose of this study was to determine if body-worn sensors detected any decline in gait and balance measures in people with MS over time. Twenty-seven p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 23 publications
1
64
1
2
Order By: Relevance
“…The MDC for the same test has been shown to vary substantially between populations, with clinical populations demonstrating greater MDCs, compared with healthy controls [11,12,[17][18][19]. Given that much of what we know regarding the MDC for the tests utilized in the present study were reported for populations with diagnosed pathologies, it makes direct comparisons between studies difficult.…”
Section: Test-retest Reliabilitymentioning
confidence: 93%
“…The MDC for the same test has been shown to vary substantially between populations, with clinical populations demonstrating greater MDCs, compared with healthy controls [11,12,[17][18][19]. Given that much of what we know regarding the MDC for the tests utilized in the present study were reported for populations with diagnosed pathologies, it makes direct comparisons between studies difficult.…”
Section: Test-retest Reliabilitymentioning
confidence: 93%
“…People with MS frequently have neuromuscular deficits such as ataxia, early muscle fatigue, spasticity and sensory disturbances, which limit gait and considerably affect their everyday living activities [1]. Subtle walking difficulties, such as reduced walking speed, step length, cadence and increased step width can be detected at an early stage of the disease [2,3,4,5]. Walking limitations have negative consequences in activities of daily living, quality of life, as well as employment etc.…”
Section: Introductionmentioning
confidence: 99%
“…Like in many neurological disorders, such evaluations are typically approached by direct observation of the clinician supported by a timed analysis, functional scales and questionnaires. Information derived from neurological assessment is included in the expanded disability status scale (EDSS) and it is most widely used to evaluate disability in MS, in both daily clinical practice and trials [2,3,5]. However, it is essential to find new tools, complementary to the clinical scales, able to supply objective and quantitative data useful in supporting clinical assessment of the disability as well as its variations across time.…”
Section: Introductionmentioning
confidence: 99%
“…Em um estudo recente Spain et al 70 , pacientes com EM também foram avaliados longitudinalmente ao longo de 18 meses (avaliações a cada 6 meses), sendo analisadas as mudanças no escore da EDSS, no tempo do T25FW, assim como nos testes de equilíbrio estático com olhos abertos e fechados, avaliados por sensores de movimento. Os Além disso, o desempenho nesses testes piora, à medida que a EDSS aumenta.…”
Section: Tabela 8 Resultado Das Correlações Entre As Alterações No Eunclassified